Naturally occurring circadian rhythm variation associated with clock gene loci in Swedish Arabidopsis accessions. (11th January 2021) - Rees, Hannah; Joynson, Ryan; Brown, James K. M.; Hall, Anthony
Abstract: Circadian clocks have evolved to resonate with external day and night cycles. However, these entrainment signals are not consistent everywhere and vary with latitude, climate and seasonality. This leads to divergent selection for clocks which are locally adapted. To investigate the genetic basis for this circadian variation, we used a delayed fluorescence imaging assay to screen 191 naturally occurring Swedish Arabidopsis accessions for their circadian phenotypes. We demonstrate that the period length co‐varies with both geography and population sub‐structure. Several candidate loci linked to period, phase and relative amplitude error (RAE) were revealed by genome‐wide association mapping and candidate genes were investigated using TDNA mutants. We show that natural variation in a single non‐synonymous substitution within COR28 is associated with a long‐period and late‐flowering phenotype similar to that seen in TDNA knock‐out mutants. COR28 is a known coordinator of flowering time, freezing tolerance and the circadian clock; all of which may form selective pressure gradients across Sweden. We demonstrate the effect of the COR28 ‐58S SNP in increasing period length through a co‐segregation analysis. Finally, we show that period phenotypic tails remain diverged under lower temperatures and follow a distinctive "arrow‐shaped" trend indicative of selection for a cold‐biased temperature compensation response. Abstract : Circadian rhythms in Swedish Arabidopsis accessions vary with both geographical regions and population structure. Through GWA mapping, we find naturally occurring period length variation is associated with a single SNP within COR28 . Finally, we show that phenotypic tails for period remain diverged at reduced temperatures and follow a distinctive arrow‐shaped trend.